Pediatric dentists' participation in advocacy and acceptance of new medicaid children in clinical practice - Singh, Arjun Deo; Lavin, Jenna; DiStefano, Caitlin; Chon, Eun; Weinstein, Stephanie; Slutsky, Samantha; Bhoopathi, Vinodh (Frontiers in Oral Health, 2022)
Introduction Advocacy involves promoting a noble cause or voicing on behalf of a program, policy, or population group. Previous literature shows that dentists who provide services to Medicaid-enrolled, underserved, and vulnerable children are more compassionate than those who do not. Aim To explore the association between pediatric dentists' (PDs) participation in various advocacy-related activities (ARAs) and their monthly acceptance of new Medicaid-enrolled children in their clinical practice to provide dental care services. Methods A 14-item pilot-tested survey was created on the SurveyMonkey® online platform and emailed to 5591 PDs, active American Academy of Pediatric Dentistry members. Data from 789 PD respondents were analyzed. Frequencies, percentages, means, and standard deviations were used to describe the sample. Independent t-tests and chi-square tests assessed the differences between PDs accepting new Medicaid-enrolled children in their clinical practice every month vs. PDs who did not. A multivariable adjusted logistic regression model determined if there was an association between PDs' participation in ARAs and their acceptance of new Medicaid-enrolled children in their clinical practice, controlling for other independent variables. Results The mean number of different ARAs performed by PDs was 2.2 ± 1.8. Approximately 65% reported that they accepted new Medicaid-enrolled children every month in their dental clinic to provide dental care services. The multivariable logistic regression model showed that the odds of a PD accepting new Medicaid-enrolled children every month increased by 13% for each additional unit increase in ARA completed, with other variables being held constant (Odds ratio: 1.13, 95% CI: 1.03–1.25, p = 0.01). Conclusion PDs who performed more ARAs had greater odds of accepting new Medicaid-enrolled children into their dental practice every month. Education and training in oral health advocacy during dental education for dental students may promote performing ARAs and providing dental care services to Medicaid patients after graduation.